2012
DOI: 10.1128/aem.07420-11
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Diversities and Community Structure of Members of the Extremely Halophilic Archaea (Order Halobacteriales) in Multiple Saline Sediment Habitats

Abstract: We investigated the phylogenetic diversity and community structure of members of the halophilic Archaea (order Halobacteriales) in five distinct sediment habitats that experience various levels of salinity and salinity fluctuations (sediments from Great Salt Plains and Zodletone Spring in Oklahoma, mangrove tree sediments in Puerto Rico, sediment underneath salt heaps in a salt-processing plant, and sediments from the Great Salt Lake northern arm) using Halobacteriales-specific 16S rRNA gene primers. Extremely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 64 publications
(106 reference statements)
6
62
0
1
Order By: Relevance
“…Moreover, a number of putative archaeal OTUs associated with the redox transition zone and monimolimnion (depths of 33 m to 120 m) were identified with "no blast hits" using Greengenes but assigned to Halobacteriales using SILVA. Because both databases are not well annotated for Halobacteria (31), the Sakinaw Lake data set was mapped onto the full-length Halobacteria SSU rRNA gene database generated by Youssef and colleagues (31) using the program CD-HIT (cd-hit-est-2d) (32). The data set could not be clustered with the Halobacteria reference sequences at 99%, 97%, or 95% identity.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a number of putative archaeal OTUs associated with the redox transition zone and monimolimnion (depths of 33 m to 120 m) were identified with "no blast hits" using Greengenes but assigned to Halobacteriales using SILVA. Because both databases are not well annotated for Halobacteria (31), the Sakinaw Lake data set was mapped onto the full-length Halobacteria SSU rRNA gene database generated by Youssef and colleagues (31) using the program CD-HIT (cd-hit-est-2d) (32). The data set could not be clustered with the Halobacteria reference sequences at 99%, 97%, or 95% identity.…”
Section: Methodsmentioning
confidence: 99%
“…Members of the class Halobacteria are extremely halophilic and haloalkaliphilic (Brito-Echeverria et al 2011;Youssef et al 2012). Members of the genus Halorubrum are ubiquitous halophilic, aerobic archaeans that inhabit saline and hypersaline soils (Papke et al 2004).…”
Section: Archaeamentioning
confidence: 99%
“…In most cases only a few soil samples of a single specific saline system, or a small number of cloned sequences or DGGE bands, have been investigated and analyzed. Some studies have focused only one particular microbial group such as Archaea (Valenzuela-Encinas et al 2009;Youssef et al 2012) or Actinobacteria (Singh et al 2012). Numerous sequences recovered from saline soils are available from the GenBank, but many of these are largely overlooked because they are not published in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…As these electron acceptors are present in hypersaline anoxic habitats at very low concentrations (Oren, 2011), it might appear that these facultative anaerobes cannot play a significant role in anaerobic environments. Nonetheless, molecular ecology studies demonstrated that highly reduced sulfur-rich hypersaline sediments and salt deposits are inhabited by haloarchaea with no cultured representatives (Walsh et al, 2005;Youssef et al, 2011). Can these organisms use elemental sulfur, which may be very abundant, as the alternative terminal electron acceptor?…”
Section: Introductionmentioning
confidence: 99%